The influence of various factors on corrosion of mild steel in deep eutectic solvents. (2019) - Rublova, Y.D.; Kityk, A.A.; Bannyk, N.G.; Protsenko, V.S.; Danilov, F.I.
Abstract: This work describes the corrosion behaviour of mild steel in deep eutectic solvents (DES) based on choline chloride, ethaline and reline. The crucial factor determining the rate of corrosion of steel in ethaline and reline is water content. It has been found that ethaline solvent is more corrosive to steel than reline when the content of extra water does exceed ca. 50 vol. %. However, if the content of water increases (more than 50 vol. %), reline becomes more corrosion-active.